Hubungan Job Characteristic terhadap Turnover Intention pada Karyawan - Mukhaira El Akmal; Rislisa Rislisa (Universitas Medan Area, 2018)
One of the factors that influence turnover intention is job characteristic. This study is aimed to determine the relationship of job characteristic to employee turnover intention in PT. XY. Hypothesis that proposed in this research is that there is a relationship between job characteristic and turnover intention. 60 Workers from PT. XY participated in this study which obtained by total sampling technique. Data is obtained from the scale to measure job characteristic and turnover intention. A Product moment correlation test was used to analyze the data. The result of data analysis shown that the correlation coefficient is -0.524 with sig. of 0.000 (p <0.05). This study shows that there is a negative relationship between job characteristic to turnover intention and the effective correlation (contribution) that is given from turnover intention is 27.5% and the other 72.5% is affected by other factors. Base on the result ini this study, it can be concluded that the hypothesis is accepted and there is a relationship between job characteristic and turnover intention.